2016
DOI: 10.1016/j.ajpath.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Proatherosclerotic Effect of the α1-Subunit of Soluble Guanylyl Cyclase by Promoting Smooth Muscle Phenotypic Switching

Abstract: Soluble guanylate cyclase (sGC), a key enzyme of the nitric oxide signaling pathway, is formed as a heterodimer by various isoforms of its α and β subunit. GUCY1A3, encoding the α1 subunit, was identified as a risk gene for coronary artery disease and myocardial infarction, but its specific contribution to atherosclerosis remains unclear. This study sought to decipher the role of Gucy1a3 in atherosclerosis in mice. At age 32 weeks and after 20 weeks of standard or high-fat diet, Gucy1a3(-/-)/Ldlr(-/-) mice exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…While a low concentration (0.5 µM) of the NO donor diethylenetriamine NONOate (DETA-NO) enhanced proliferation via a cGKI-dependent pathway, high concentrations of DETA-NO (100 µM) strongly reduced VSMC growth independent of cGKI. A cGMP-independent, anti-proliferative effect of NO in VSMCs was also observed by other groups [ 50 , 69 ]. In sum, there is strong evidence that low/physiological NO concentrations promote VSMC growth via the cGMP-cGKI axis, whereas high/pathophysiological concentrations of NO inhibit VSMC growth in a cGMP/cGKI-independent manner.…”
Section: Cgmp and Vsmc Plasticity In Cell Culturesupporting
confidence: 79%
See 1 more Smart Citation
“…While a low concentration (0.5 µM) of the NO donor diethylenetriamine NONOate (DETA-NO) enhanced proliferation via a cGKI-dependent pathway, high concentrations of DETA-NO (100 µM) strongly reduced VSMC growth independent of cGKI. A cGMP-independent, anti-proliferative effect of NO in VSMCs was also observed by other groups [ 50 , 69 ]. In sum, there is strong evidence that low/physiological NO concentrations promote VSMC growth via the cGMP-cGKI axis, whereas high/pathophysiological concentrations of NO inhibit VSMC growth in a cGMP/cGKI-independent manner.…”
Section: Cgmp and Vsmc Plasticity In Cell Culturesupporting
confidence: 79%
“…Studies with cultured VSMCs have linked components of the cGMP signaling pathway to VSMC proliferation and marker protein expression, indicating a role of cGMP in phenotypic switching of VSMCs. In particular, the mechanism and therapeutic relevance of cGMP-regulated VSMC plasticity via the NO-cGMP-cGKI axis has been intensively investigated over the past few decades [ 9 , 13 , 15 , 35 , 50 , 51 , 52 ]. However, it is still debated if stimulation of this cascade inhibits or promotes the growth of VSMCs.…”
Section: Cgmp and Vsmc Plasticity In Cell Culturementioning
confidence: 99%
“…Nevertheless, the data uniformly point towards a stronger effect of NO on inhibition of migration and platelet aggregation in GUCY1A3 non-risk allele carriers. Third, a recently published paper suggests that complete knockout of Gucy1a3 in mice may reduce atherosclerotic plaque formation on a proatherogenic background ( Ldlr −/− ) 37 . In contrast to this study, we and others investigated a partial loss of sGC activity and showed experimentally in mice and functionally in human materials that this leads to increased disease risk 10,3840 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this study, we and others investigated a partial loss of sGC activity and showed experimentally in mice and functionally in human materials that this leads to increased disease risk 10,3840 . Thus, in the total Gucy1a3 knockout model compensatory mechanisms affecting NO/cGMP signaling, including a marked compensatory increase of Gucy1a2 expression in Gucy1a3 −/− VSMC 37 , may not have been adequately addressed. Indeed, the total knockout of genes might be more useful to investigate molecular mechanisms rather than complex diseases such as atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using sGCα1 KO mice crossed with LDLr KO mice have shown surprisingly a decrease in plaque burden compared to LDLr KO alone. The authors suggest that PKG increases smooth muscle proliferation and that this underlies the apparent benefits of deletion of the gene by triggering a switch in smooth muscle cell phenotype (40). Interestingly the authors only consider that such an effect is detrimental; however, of course in the atherosclerotic scenario, a stimulus that is antiinflammatory but at the same time increases smooth muscle content of a plaque would be, in the long term, beneficial in terms of switching a plaque from an unstable to a stable phenotype.…”
Section: Discussionmentioning
confidence: 99%